2011
DOI: 10.1016/j.gde.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense-mediated mRNA decay (NMD) in animal embryogenesis: to die or not to die, that is the question

Abstract: SUMMARY Nonsense-mediated mRNA decay (NMD) is a well-studied cellular quality-control pathway. It decreases the half-lives of eukaryotic mRNAs that aberrantly contain premature termination codons and additionally regulates an estimated 10–20% of normal transcripts. NMD factors play crucial roles during embryogenesis in many animals. Here, we review data indicating that NMD factors are required for proper embryogenesis by discussing the abnormal developmental phenotypes that result when the abundance of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
121
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 81 publications
(104 reference statements)
1
121
0
Order By: Relevance
“…The NMD pathway is required for organismal development as well as in several tissue-and condition-specific contexts, suggesting a regulatory role extending beyond a general surveillance mechanism (Hwang and Maquat 2011). Several recent studies have highlighted the specific contribution of AS-NMD to the regulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The NMD pathway is required for organismal development as well as in several tissue-and condition-specific contexts, suggesting a regulatory role extending beyond a general surveillance mechanism (Hwang and Maquat 2011). Several recent studies have highlighted the specific contribution of AS-NMD to the regulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the NMD-specific function of PABP has proven to be difficult to study separately from its other important functions in mRNA translation and stabilization. Furthermore, human NMD is characterized by different signals for NMD activation and multiple pathways for degradation, contrary to many other organisms that use one main NMD mechanism (Hwang and Maquat 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NMD directly or indirectly regulates the expression of many physiological mRNAs, although only some of them contain PTCs, for example, as a result of alternative splicing or upstream open reading frames (Yepiskoposyan et al 2011;Tani et al 2012). The function of NMD as a general regulator of gene expression explains why NMD factors are essential for normal animal development (Hwang and Maquat 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The malfunction of NMD factors results in serious consequences for the development of various organisms. 17 Genome-wide analysis using DNA microarrays suggested that NMD regulates 3-20% of transcripts in yeast, 18 nematode, 19 fruitfly, 20 plants 21 and mammals. [22][23][24][25][26][27] Genome-wide RNA half-life analysis also identified the transcripts dysregulated in response UpF1 eliminates aberrant mRNAs harboring premature termination codons, and regulates the steady-state levels of normal physiological mRNAs.…”
Section: Introductionmentioning
confidence: 99%